2015
DOI: 10.1007/s13278-015-0287-8
|View full text |Cite
|
Sign up to set email alerts
|

Start-up firms’ networks for innovation and export: facilitated and constrained by entrepreneurs’ networking in private and public spheres

Abstract: Research on how start-up firms utilize networks has focused on direct effects of either the personal network around the entrepreneur or the formal collaboration network around the firm. Combining those approaches, we model how a firm's collaboration network is embedded in the personal network around the entrepreneur. With data from the Global Entrepreneurship Monitor on 8918 start-up firms in 40 countries surveyed during 2012-2013, we examine (1) how entrepreneurs' networking in private and public spheres is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
6
18
1
Order By: Relevance
“…• Firm size positively linked to export level Our results corroborate those of the study 8,918 start-up firms in 40 countries GEM 2012-2013 (Jensen and Schott, 2015) • Innovation impacts positively export level…”
Section: Study and Sample Results Our Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…• Firm size positively linked to export level Our results corroborate those of the study 8,918 start-up firms in 40 countries GEM 2012-2013 (Jensen and Schott, 2015) • Innovation impacts positively export level…”
Section: Study and Sample Results Our Resultssupporting
confidence: 87%
“…Our model shows the positive effect of innovation on the level of firms' exports, so our results are supported by previous research (Caldera, 2010;Filipescu et al, 2013;Jensen and Schott, 2015;Lachenmaier and Wößmann, 2006;Pla-Barber and Alegre, 2007). The authors confirm the innovation-export causality in Western countries.…”
Section: Discussionsupporting
confidence: 90%
“…Friendship ties, however, does not necessarily lead to cooperation in a horizontal relationship. This is the case of MA13, whose respondent said they "exchanged information … but informally" with competitors, which corroborates with the research by Jensen and Schott (2015). It is understood that the inter-organizational relationships in this industry are informal, and the partnerships are maintained because of friendship ties.…”
Section: Positioning/power/personal Positioning/attributessupporting
confidence: 83%
“…On the other hand, Jensen and Schott (2015) observe that the relationships with family and friends reduce the extension of the network of firms, negatively impacting the increase of innovation in the firms of the network. In the Amazon bioindustry, Andrade (2017) identified that entrepreneurs do not feel secure in partnerships with firms of the same activity, despite the need to increase their production capacities, market share, and exploration Interorganizational Relationships in the Amazon Biotech Industry Based on Entrepreneurs´ Perceptions 677 RAC, Maringá, v. 23, n. 5, SI Technology Amazon, art.…”
Section: Relational Factors Of An Inter-organizational Relationshipmentioning
confidence: 96%
“…They can consist of high transaction costs and the challenges of achieving tacit knowledge (Dhanaraj & Parkhe, 2006) or the risk of malfeasance (Dyer & Singh, 1998). Furthermore, relational experience, trust, and reciprocity might stimulate inter-firm complementarity and shared understandings, and thereby reduce cognitive barriers to knowledge transfer and enhance the benefits of inter-firm relationships (Jensen & Schøtt, 2015). It can be seen that there is a great deal of theoretical and empirical evidences on the associations between networks and innovations.…”
Section: Networkmentioning
confidence: 99%